Analisis Komunikasi Beban Kerja Air Traffic Controller (ATC) dalam Menjaga Keselamatan Lalu Lintas Penerbangan di Airnav Indonesia Cabang Palembang - Hendiyanto; Isnawijayani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
As a fast, economical and efficient transportation alternative, air transportation is the only alternative for inter-island and inter-regional transportation. Air transportation itself has Air Traffic or flight traffic which must be obeyed by all vehicles on the ground and in the air such as commercial airplanes, helicopters and the like. This research aims to investigate the role of communication in managing the Air Traffic Controller (ATC) workload in maintaining flight traffic safety at AirNav Indonesia Palembang Branch. Increasingly dense and complex air traffic requires effective coordination and communication between ATC and aircraft pilots to prevent incidents and accidents. The research method uses a qualitative approach involving in-depth interviews with ATC, observations at the air traffic control center, and analysis of related documents. The results of this research reveal that good communication between ATC and pilots is very important in maintaining flight safety. ATCs must manage their workload carefully, including managing communications as diverse as voice communications, text messages, and radar data. Additionally, factors such as time pressure, fatigue, and stress also influence ATC communications. Workload management and good training to improve ATC communication capabilities are necessary. This study also provides recommendations for developing policies and best practices in optimizing ATC communications in maintaining flight safety at AirNav Indonesia Palembang Branch.